Synthesis of MCM‐41@SO3H‐Polymixin B Nanocomposite for Extraction and Determination of Lipopolysaccharide from Aqueous Solutions using Taguchi Fractional Factorial Design. Issue 45 (1st December 2022) - Hedayati Ch, Mojtaba; Mehmandoost Du, Edris; Golshekan, Mostafa; Mojtahedi, Ali; Mobayen, Mohammadreza
Abstract: Lipopolysaccharide (LPS) is a component of Gram‐negative bacteria's outer membrane that, when released into aqueous solutions, can have devastating consequences for human health. In this study, sulfonic acid‐functionalized mesoporous silica nanocomposites bound to polymixin‐B was synthesized and their functionality to absorb the bacterial LPS from human serum was investigated. Briefly, Pseudomonas aeruginosa was isolated from burn wounds and its LPS was extracted. Then, Mesoporous MCM‐41 nanocomposites were fabricated and functionalized with the sulfonic acid groups. Finally, nanocomposites were used to extract LPS from human serum and statistical data were analyzed using the Taguchi method. Extraction of bacterial LPS with a modified method, optimization of factors affecting the extraction of endotoxin using Taguchi method, introduction of new nano‐composites with nanometer pores and obtaining results with 96 % effectiveness in removing LPS in LAL and MTT tests were the most important findings. The obtained calibration curve was linear in the ranges of 1–300 μg L‐1 with reasonable linearity (r2>0.998). The limit of detection (LOD) based on S/N=3 was 0.03 μg L‐1 for 10 mL sample volumes. Abstract : We report, synthesis of MCM‐41@SO3H‐polymixin organic–inorganic nano composite. The synthesized nano‐composite is specific adsorption for bacterial LPS. The synthesized nanocomposite is very stable and can be reused for several times.